Free Speech v. Free Blacks: Racist policing and calls to harm. Issue 2 (2nd July 2020) - Hill, Annie
ABSTRACT: In 2018, mobile phone videos went viral of white people calling police to report Black people for engaging in innocuous conduct. Dubbed "white caller crime" by some commentators, mainstream and social media afforded serious and satiric attention to racist harassment via police calls. In this article, I analyze these police calls as a form of racist expression that operates as a call to harm . I begin by recounting three calls that went viral in consecutive months in 2018. I then theorize how the calls play out white supremacist and colonial logics of race and place, and I explore how viral publicity provides a viable strategy of resistance to racist expression. I close by contending that publicity, and the responses it has inspired, holds more promise for contesting racist police calls than a predictable turn to law and punishment under a hate speech framework.